2020
DOI: 10.3390/cells9102243
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Low-Dose Delta-9-Tetrahydrocannbinol (THC) Administration to Simian Immunodeficiency Virus (SIV) Infected Rhesus Macaques Stimulates the Release of Bioactive Blood Extracellular Vesicles (EVs) that Induce Divergent Structural Adaptations and Signaling Cues

Abstract: Blood extracellular vesicles (BEVs) carry bioactive cargo (proteins, genetic materials, lipids, licit, and illicit drugs) that regulate diverse functions in target cells. The cannabinoid drug delta-9-tetrahydrocannabinol (THC) is FDA approved for the treatment of anorexia and weight loss in people living with HIV. However, the effect of THC on BEV characteristics in the setting of HIV/SIV infection needs to be determined. Here, we used the SIV-infected rhesus macaque model of AIDS to evaluate the longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Therefore, it is worth mentioning that in two different models, bacterial-and cancer cells [12,13], CBD was able to inhibit the release of exosomes and microvesicles in vitro. Another cannabinoid, the closely related delta-9-tetrahydrocannabinol (THC) decreased extracellular vesicles in the blood of macaques infected with Simian Immunodeficiency Virus (SIV) in a pharmacological dose of 0.18 mg/ kg [14]. Furthermore, reduced plasma HIV-1 RNA viral loads have been observed in HIV-infected subjects with a heavy consumption of cannabis [15].…”
Section: Preclinical Data Suggest a Potential Benefit Of Cannabidiol mentioning
confidence: 99%
“…Therefore, it is worth mentioning that in two different models, bacterial-and cancer cells [12,13], CBD was able to inhibit the release of exosomes and microvesicles in vitro. Another cannabinoid, the closely related delta-9-tetrahydrocannabinol (THC) decreased extracellular vesicles in the blood of macaques infected with Simian Immunodeficiency Virus (SIV) in a pharmacological dose of 0.18 mg/ kg [14]. Furthermore, reduced plasma HIV-1 RNA viral loads have been observed in HIV-infected subjects with a heavy consumption of cannabis [15].…”
Section: Preclinical Data Suggest a Potential Benefit Of Cannabidiol mentioning
confidence: 99%
“…These extrinsic factors make studies with human subjects' complex, and data associated with such studies correlational. Animal models, such as the SIV-infected rhesus macaque (SIV/RM) model [18,19] of HIV provides a valuable animal model/approach and more controlled environment to study HIV-induced neuroinflammation, the response to long-term treatment with THC, and the effects of HIV/SIV alone or SIV and THC on EV cargo composition and function.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that the anti-inflammatory effects of long-term low dose THC was associated with its ability to stimulate the release of bioactive bloodderived extracellular (BEVs) [18] that induced divergent actin cytoskeletal and signaling cues in SIV-infected RMs [18]. Whether or not THC is capable of reversing neuroinflammatory effects of HIV/SIV is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations